Positive radial solutions for Dirichlet problems via a Harnack‐type inequality. (2nd September 2022) - Precup, Radu; Rodríguez‐López, Jorge
Abstract : We deal with the existence and localization of positive radial solutions for Dirichlet problems involving ϕ φ ‐Laplacian operators in a ball. In particular, p p ‐Laplacian and Minkowski‐curvature equations are considered. Our approach relies on fixed point index techniques, which work thanks to a Harnack‐type inequality in terms of a seminorm. As a consequence of the localization result, it is also derived the existence of several (even infinitely many) positive solutions.